Aristotle's hermeneutic model: the legal thinking and the theory about judgement - Гетьман, І. В. (Problems of legality, 2013)
Article is devoted the system analysis of one of actual methodology − to hermeneutics. Research begins with a historical context in which the first knowledge about the general theory of understanding − hermeneutics arose. In article gnoseological research of knowledge of a hermeneutic problematics of the universal philosopher of an epoch of antiquity − Aristotle is made, the attention in particular is paid to its ideas concerning construction of the separate theory about judgement, to preconditions and process of formation of philosophical and legal thinking, as component of the first.